Numerical Investigation of Turbine Blades with Leading-Edge Tubercles in Uniform Current - Shuling Chen; Yan Liu; Changzhi Han; Shiqiang Yan; Zhichao Hong (Water, 2021)
Inspired by the tubercles on humpback whale flippers, leading-edge tubercles have been incorporated into the design of wings and turbine blades in an attempt to improve their hydrodynamic performance. Although promising improvements, especially in terms of the stall performance, have been demonstrated in the limited research that exists to date, the effectiveness of the leading-edge tubercles seems to be influenced by the base blade. This paper focuses on the introduction of sinusoidal leading-edge tubercles to a base blade developed from the classic NACA0018 airfoil, and numerically investigates the effectiveness of leading-edge tubercles on the hydrodynamics associated with the blade in uniform current with different attack angles. Both the macroscopic parameters, such as the lift and drag forces, and the micro-scale flow characteristics, including the vortex and flow separation, are analyzed. The results indicate that the leading-edge tubercles brings a significant influence on the hydrodynamic forces acting on the blade when subjected to an attack angle greater than 15°. This study also reveals the important role of the turbulence and flow separation on hydrodynamic loading on the blade and the considerable influence of the tubercles on such micro-scale flow characteristics. Although the conditions applied in this work are relatively ideal (e.g., the blade is fixed in a uniform flow and the end effect is ignored), the satisfactory agreement between the numerical and corresponding experimental data implies that the results are acceptable. This work builds a good reference for our future work on the hydrodynamic performance of tidal turbines which adopt this kind of blade for operating in both uniform and shearing currents.